The impact of the belt and road initiative on China’s international air transport: Evidence from a difference-in-differences approach - Zhang, Hongyu; Bai, Yang (Asian Journal of Economics and Empirical Research, 2026)
This study examines the impact of the Belt and Road Initiative (BRI) on international air transport supply in China. Using panel data from 69 Chinese cities over the period 2007–2019, a multi-period difference-in-differences (DID) model is employed to identify the causal effects of the policy. The results show that the BRI significantly increases international air transport capacity, as measured by available seat kilometers (ASK) and seat capacity. The findings remain robust after a series of tests, including parallel trend analysis, placebo tests, and propensity score matching (PSM-DID). Further heterogeneity analysis reveals that the policy effects are more pronounced in non-hub cities and western regions, indicating stronger marginal impacts in areas with relatively weaker aviation foundations. These results suggest that the BRI plays an important role in enhancing international connectivity and promoting more balanced development of China’s aviation network. The study provides empirical evidence for policymakers to optimize aviation resource allocation and improve regional integration under the BRI framework.